Intracellular thermal sensor for single cell analysis-short review - Binslem, Salma Abdullah (Penerbit UTM Press, 2015)
Temperature is a key environmental variable that affects almost all natural and engineered systems from the system level down to the molecular level. The first attempt to measure temperature goes back to 1592 when Galileo Galilei tried to develop a thermometer. Since then having accurate temperature measurements has been a challenging research topic. Recently, in single cell analysis, internal temperature and heat generation inside a living cell has proven to have important roles in the survival of cells, controls many cellular activities for instance; cell division and gene expression. Moreover, cancerous cells are identified with excessive heat production. Studies have been done by researchers from different fields in the attempt to develop sensors that can accurately report the temperature inside living cells. This short review presents the most recent developments in nanoscale thermometry for biological applications, highlighting the recent advances in the near field and the far field methods. The far field thermometry cover sensors that depend on the luminescence’s of the material, for example: quantum dots, nanoparticles, and fluorescents based compounds. While, near field thermometry is based on different principles depending on the sensing mechanism used. Some of the examples mentioned are thermocouple thermometry, RNA thermometry, resonant thermometry, photoacoustic thermometry and carbon nanotubes thermometry.